La réécriture du mythe d’Ulysse dans le roman migrant. Errances de Sergio Kokis - Sadkowski, Piotr (Romanica Silesiana)
The article focuses on the analysis of Sergio Kokis’ novel “Errances” as an example of contemporary transvalorization of the myth of Odysseus. Kokis’ novel is treated as a „récit odysséen” (an „Odyssean narrative”), i.e. a type of fiction characterized by the theme of an exile’s return to the native land and the exploration of the protagonist’s narrative identity by means of metafictional devices. In the process of rewriting the Homeric epic and 20th century versions of the myth of Odysseus (Nikos Kazantzakis’ “The Odyssey: A Modern Sequel” and Joseph Conrad’s novels), Sergio Kokis deconstructs the concept of the return to the native land defined in terms of territory and ethnicity. What emerges from the novel, is a concept of the ethos of the eternal wanderer based on the shattering of the illusion of collective belonging as the source of identity. Key words: Odysseus; transvalorization; narrative identity; return